(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
أجريت هذه الدراسة خلال موسمي 2005-2006. تم جمع العينات من بساتين حمضيات تابعة لقرى محافظة اللاذقية (البصة, اسطامو, طرجانو, حميميم). هدفت هذه الدراسة إلى تحديد الأعداء الحيوية المرافقة لحشرة الحمضيات القشرية الأرجوانية Lepidosaphes beckii (Newman) وتعريفها وتحديد المتطفل الأكثر انتشارا. حيث تم تسجيل 7 أنواع من المتطفلات الحشرية المرافقة لحشرة الحمضيات الأرجوانية في مناطق الدراسة تتبع هذه المتطفلات لرتبة غشائيات الأجنحة Hymenoptera فوق فصيلة Calcidoidea فصيلة Aphelinidae أربعة من هذه المتطفلات خارجية التطفل Exoparasitoids تتبع الجنس Aphytis، ومتطفلان داخليان يتبعان للجنس Encarsia، وتم تسجيل 6 مفترسات 4 منها تتبع رتبة Coleopteraوهي: Linnaeus Chilocorus bipustulatus، Exochomus quadripustulatus (Linnaeus) Rhyzobius lophanthae (Blaisdell) ، de Marseul Scymnus syriacus. ومفترس من رتبة Neuroptera هو Stephens Chrysoperla carnea ومفترس من رتبة Hemipteraهو Orius sp. This study was conducted during 2005-2006. Samples were collected from citrus orchards in Lattakia governorate (Albassa, Stamo, Tergano, and Hmemim). The aim of this study is to determine natural enemies associated with lepidosaphes beckii. During this study, seven parasitoids were found associated with purple scale. These parasitoids belong to Hymenoptera: Calcidoidea: Aphelinidae. Four of them are ectoparasitoids: Aphytis spp. Two of them are endoparasitoids: Encarsia spp., and six predators belong to Coleoptera: Chilocorus bipustulatus, Exochomus quadripustulatus (Linnaeus) Rhyzobius lophanthae (Blaisdell), de Marseul Scymnus syriacus Stephens, Chrysoperla carnea, Linnaeus. Neuroptera and Hemiptera Orius sp. were found